Religiosity and Substance Use Among Youth in Southeast Europe: The Importance of God as the Strongest Protective Religious Dimension - Lavrič, Miran (Journal of drug issues, 2023)
Using a large sample of youth (N = 10,398) from 10 countries of Southeast Europe, the present study analyzed the effects of different dimensions of religiosity on various types of substance use across three different religions. The results, based on risk ratios and binary logistic regression, indicated that belief in the importance of God is generally a much stronger protective factor against substance use than church attendance or personal prayer. At the level of the entire sample, risk ratios revealed that finding God to be highly important reduced the likelihood of using hard drugs by as much as 69% and the likelihood of using soft drugs by 74%. In the case of alcohol use, the effect was weaker and less robust. Overall, the results of this study results point to the high relative importance of belief in God as a factor strengthening an individual’s ability to refrain from substance use.